Redundancy and modularity in membrane-associated dissimilatory nitrate reduction in Bacillus - Heylen, Kim; Keltjens, Jan (Frontiers in Microbiology, 2012)
The genomes of two phenotypically denitrifying type strains of the genus Bacillus were sequenced and the pathways for dissimilatory nitrate reduction were reconstructed. Results suggest that denitrification proceeds in the periplasmic space and in an analogous fashion as in Gram-negative organisms, yet with the participation of proteins that tend to be membrane-bound or membrane-associated. A considerable degree of functional redundancy was observed with marked differences between B. azotoformans LMG 9581T and B. bataviensis LMG 21833T. In addition to the already characterized menaquinol/cyt c-dependent nitric oxide reduction (Suharti et al., 2001;Suharti et al., 2004) of which the encoding genes could be identified now, evidence for another novel nitric oxide reductase was found. Also, our analyses confirm earlier findings on branched electron transfer with both menaquinol and cytochrome c as reductants. Quite unexpectedly, both bacilli have the disposal of two parallel pathways for nitrite reduction enabling a life style as a denitrifier and as an ammonifying bacterium.